Dynamic Interactive Social Cognition Training in Virtual Reality (DiSCoVR) for adults with Autism Spectrum Disorder: A feasibility study. (August 2022) - van Pelt, B.J.; Nijman, S.A.; van Haren, N.E.M.; Veling, W.; Pijnenborg, G.H.M.; van Balkom, I.D.C.; Landlust, A.M.; Greaves-Lord, K.
Abstract: Background: Social cognitive difficulties in Autism Spectrum Disorder (ASD) can affect the daily lives of people with ASD profoundly, impacting the development and maintenance of meaningful social relations. Social cognition training (SCT) is commonly used for improving social functioning, but lacks ecological validity and the ability to effectively mimic social situations. Development of virtual reality (VR) interventions, focusing on enhancing social cognition, could add to the effectiveness of SCT within ASD care, by offering a safe, interactive and practical training setting, where generalization of knowledge and skills to the real-world are promoted. In this paper, our primary aim is to evaluate the feasibility and acceptance by participants and therapists of the Dynamic Interactive Social Cognition Method: Training in Virtual Reality (DiSCoVR) protocol as developed for adults with schizophrenic spectrum disorder (SSD), adapted for ASD (DiSCoVR-A). 26 participants, aged 18–63, took part in a pilot study. 22 participants completed baseline and post-assessment, including primary outcome evaluation assessment through a semi-structured interview. Secondary measures focused on social cognition, emotion recognition, mental flexibility, social anxiety, empathy and social responsiveness and were assessed at baseline (T0 ), post-treatment (T1 ), and at follow-up (T2 ) sixteen weeks after completion of the intervention. Results: Our results show that the majority of participant and therapists found the VR intervention acceptable and feasible, as reported in evaluation questionnaires and interviews. Conclusion: These preliminary findings are promising; however, controlled research is needed to further investigate the effectiveness of VR within social cognition training for adults with ASD. Highlights: Social cognitive deficits in Autism Spectrum Disorder (ASD) can affect the daily lives of people with ASD profoundly. Enhancing social cognitive skills through Virtual Realitycould add to the effectiveness of social cognition training. VR offers a safe and practical training setting, where generalization of knowledge/skills to the real-world are promoted. This study shows that the virtual reality social cognition training is feasible as a training tool for people with autism. The virtual reality training was well accepted by both therapists and patients.